On the benefits of point-to-multipoint coherent optics for multilayer capacity planning in ring networks with varying traffic profiles - Pavon-Marino, P.; Skorin-Kapov, N.; Bueno-Delgado, M. V.; Back, J.; Napoli, A. (Journal of optical communications and networking, 2022)
Point-to-multipoint (P2MP) coherent optics using digital subcarrier multiplexing have recently been proposed as a promising new technology to reduce the cost and complexity of optical transport networks, particularly those in metro aggregation scenarios with hub-and-spoke (H&S) traffic patterns. In this paper, we perform a case study on fault tolerant ring networks with more general traffic profiles to assess the benefits of P2MP optics for alternative network scenarios such as those appearing in metro rings. We propose mixed integer linear programming formulations for multilayer capacity planning to minimize total transceiver costs, considering both point-to-point and P2MP transceivers, as well as a heuristic approach for the more complex P2MP case. Results indicate that P2MP optics can bring several advantages for all tested traffic profiles, ranging from pure uniform flows to mostly H&S. Transceiver cost savings are achieved in various cases, greater at higher network loads and for traffic patterns that are mostly H&S. Results also show that P2MP optics prompt a multilayer redesign of the network with significantly reduced spectrum usage and a reduced number of IP hops, resulting in lower optical–electronic–optical and IP processing latency and lower IP layer equipment costs for all traffic profiles.